2012
DOI: 10.1080/08927014.2012.695351
|View full text |Cite
|
Sign up to set email alerts
|

Formation of bacterial streamers during filtration in microfluidic systems

Abstract: Bacterial behavior during filtration is complex and is influenced by numerous factors. The aim of this paper is to report on experiments designed to make progress in the understanding of bacterial transfer in filters and membranes. Polydimethylsiloxane (PDMS) microsystems were built to allow direct dynamic observation of bacterial transfer across different microchannel geometries mimicking filtration processes. When filtering Escherichia coli suspensions in such devices, the bacteria accumulated in the downstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
64
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 24 publications
6
64
0
Order By: Relevance
“…Other systems that suffer from biofilm-induced clogging are spiral-wound reverse osmosis filters (48,49), which are used, e.g., to purify drinking water. Feed spacer mesh, the element within these filtration devices that is prone to biofilm formation, also displays biofilm streamers that form a network (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Other systems that suffer from biofilm-induced clogging are spiral-wound reverse osmosis filters (48,49), which are used, e.g., to purify drinking water. Feed spacer mesh, the element within these filtration devices that is prone to biofilm formation, also displays biofilm streamers that form a network (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…They found that the streamers can form in curved sections of microchannels, and streamer morphology is related to motility. Recent research has demonstrated that streamers can have wide repercussions in various natural and artificial scenarios as they can act as precursors to the formation of mature structures in porous interfaces, lead to rapid and catastrophic biofilm proliferation in a biomedical systems, and also cause substantial flow-structure interactions, etc 1,[7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we found that biofilm streamers develop rapidly following inoculation and they span the gaps in a complex, branched channel. This example indicates that biofilm streamers might be universal in porous media in environmental and medical environments (48, 78-80), where they could cause rapid clogging.…”
Section: Resultsmentioning
confidence: 98%